ANALISIS STRUKTUR ATAS GEDUNG ASRAMA PUTRI KAMPUS II SMKKN MANOKWARI MENGGUNAKAN METODE KEKUATAN BATAS - Ramla Arfayani Umarella; Pieter Lourens Frans; Delvia Rimesye Apalem (JURNAL SIMETRIK, 2026)
A building structure is an assembly and arrangement of various elements designed in such a way that it can withstand external and self-loads without experiencing deformation beyond allowable limits. The construction of the female dormitory building at Campus II of SMKKN Manokwari has not yet been carried out according to the plan; therefore, a structural analysis is necessary to determine the magnitude of the internal forces acting and the reinforcement system. The method used is the limit strength method with the assistance of SAP2000 v.22 software. Based on the analysis results, the forces acting on the cross-section are an average support moment of 56.33 kN·m, an average field moment of 34.28 kN·m, an average shear force of 72.81 kN, and an axial force on the column of 250.08 kN. The reinforcement calculations resulted in reinforcement for the column, beam, and slab cross-sections using D16 bars, with shear reinforcement using Ø10 bars, thus classifying the cross-section as under-reinforced.  Keywords : Internal forces, Structure, Ultimate strength